Mendidik Anak Usia Dini Berdasarkan Teori Albert Bandura: Penerapan “Habitus“ Perilaku - Pasiska, Pasiska (Bouseik: Jurnal Pendidikan Islam Anak Usia Dini, 2024)
The writing is aimed at knowing the method of educating children in accordance with the Hadith the Messenger of Allah based on theory of Albert Bandura. With a focus toward early childhood, by applying behavioral conditioning taught parents, who act as a "model" with the Messenger as a "model". Expected with the conditioning methods that comply with Islamic teachings, the child is able to develop the cognitive, social and moral for the better.